The potential targets of Kupffer cells activity during liver regeneration - Obolenskaya, M.Y. (Биополимеры и клетка, 1997)
This paper addresses possible causal and kinetic correlations between production of biologically active molecules by Kupffer cells and biochemical events in regenerating liver after partial hepatectomy. The expression and activity of some genes and enzymes were evaluated that are potential targets for regulation by Kupffer cells, e. g. transcriptional factors coded by the nuclear protooncogenes, c-fos and c-myc, a tissue-specific gene P450IIE1 and 2'5'oligo(A) synthetase. The results were compared with data about Kupffer cell activity during regeneration. Kupffer cells manifest their specific activities during transition of hepatocytes from quiescence to the first cell cycle and during the promotion of the last one. After termination of these functions the macrophages themselves enter into a cell cycle. These phenomena indicate a regulatory role of mesenchymal cells in triggering and promoting liver regeneration. Цю роботу присвячено аналізу причинно-наслідкових зв'язків та часових співвідношень між синтезом клітинами Купфера біологічно активних молекул і біохімічними процесами, що проходять у регенеруючій печінці після часткової гепатектомїі. Досліджували експресію і активність ряду генів і ферментів, які потенційно регулюються клітинами Купфера, а саме: протоонкогенів c-fos і с-тус, кодуючих транскрипційні фактори, тканиноспецифічного гена Р450ІІЕ1 і ферменту 2',5'-оліго(А)синтетази. Синтез біологічно активних молекул в клітинах Купфера є найвиразнішим у період переходу гепатоцитів від стану спокою до ділення. По мірі проходження гепатоцитами фаз клітинного циклу набір біологічно активних молекул звужується. Клітини Купфера переходять до проліферації після завершення гепатоцитами їх першого клітинного ціклу. Пропонується гіпотеза щодо регулюючої ролі клітин Купфера в запуску і розвиткові регенераційного процесу у печінці. Настоящая работа посвящена анализу причинно-следственных связей и временных соотношений между синтезом клетками Купфера биологически активных молекул и биохимическими процессами, происходящими в регенерирующей печени после частичной гепатэктомии. Исследовали экспрессию и активность ряда генов и ферментов, потенциально регулируемых клетками Купфера, а именно: протоонкогенов c-fos и с-ту с, кодирующих транскрипционные факторы, тканеспецифического гена P450IIE1 и фермента 2',5'-олиго(А)синтетазы. Результаты исследований сравнивали с данными об активности клеток Купфера во время регенерации. Синтез биологически активных молекул в клетках Купфера наиболее выражен в период перехода гепатоцитов от покоя к делению. По мере прохождения гепатоцитами фаз клеточного цикла набор биологически активных молекул сужается. Клетки Купфера переходят к пролиферации после завершения гепатоцитами их первого клеточного цикла. Предлагается гипотеза о регулирующей роли клеток Купфера в запуске и развитии регенерационного процесса в печени.